Актуальні проблеми запобігання кримінальним правопорушенням при запровадженні та вдосконаленні чинного Кримінального процесуального кодексу України - Юхно, О. О.; Yukhno, O. O.; Олександр Юхно (Вісник Кримінологічної асоціації України. - 2015. - № 2 (10). - С. 275-286., 2015)
Статтю присвячено актуальним проблемам запобігання злочинам на стадії досудового розслідування, запропонована характеристика законодавчого та нормативно-правового регулювання такої діяльності слідчими і прокурорами. Надано пропозиції щодо вирішення й удосконалення окремих питань у цьому напрямі правозастосовної діяльності та запропоновано шляхи їх вирішення.

The article is devoted to topical and urgent problems of crime prevention at the pre-trial investigation stage in the present state, especially after the adoption and implementation of the current Criminal Procedural Code of Ukraine. By the results of the study it is stressed on the importance of organization and implementation of preventive work by state, law enforcement and other authorities, public institutions in this area of activity; on the basis of scientific views of scholars and experts the suggestion to adopt national legislative act regarding the admissibility of preventive and protective work across the country and regions of Ukraine is supported. Comparative characteristics of constitutional, legislative, normative and legal regulation of such activities by investigators and prosecutors are provided; the author states scientific points of view of scholars, who have not supported the position of the legislator to abolish the relevant Articles 23, 23-1, 23-2 of the previous Criminal and Procedural Code of Ukraine of 1960 concerning the issues of establishing the causes and conditions, which contributed to the commission of criminal offences and respond of investigators, prosecutors, judges on them in the current criminal procedural legislation of Ukraine. Special attention is paid to the fact that despite these changes in the legislation, legal acts of the Ministry of Internal Affairs of Ukraine and Prosecutor General’s Office of Ukraine still stipulate the duty of investigators, prosecutors at all structural levels to organize and carry out preventive activities and respond to detected violations in order to prevent them in the future and eliminate the negative effects. Practices of investigators, prosecutors concerning the above mentioned issues are analyzed. It proves the need and feasibility of conducting such preventive activities. The propositions to address and improve specific issues in this area of law enforcement activity are provided; the ways of their solution, consolidation of the studied activity in the legislation, in particular in the criminal procedural legislation of Ukraine, as well as improving the normative and legal base of the Ministry of Internal Affairs, Prosecutor General’s Office of Ukraine and other law enforcement and state agencies are offered.

Статья посвящена проблемам предотвращения преступлений при проведении досудебного расследования в современных условиях. В ней дана характеристика законодательного и нормативно-правового регулирования такого вида деятельности следователями и прокурорами. Представлены предложения по вопросам решения и совершенствования отдельных направлений правоприменительной деятельности, а также предложены пути их решения.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; запобігання; органи досудового розслідування; прокурор; слідчий; кримінальне правопорушення; суб’єкт запобігання; причини та умови злочинності; рівень злочинності; рецидив; prevention; pre-trial investigation authorities; prosecutor; investigator; criminal offence subject of prevention; causes and conditions; crime rates; recidivism; предотвращение; предупреждение; органы досудебного расследования; прокурор; следователь; уголовное производство; уголовное правонарушение; субъект предотвращения; причины и условия преступности; уровень преступности; рецидив